Nutrient content in leaves of hydroponic lettuce (Lactuca sativa convar. capitata L.) on higher magnesium and nitrogen nutrient treatment - Vojnich, Viktor József; Hüvely, Attila; Pető, Judit; Novák, Dávid István (Acta Biologica Szegediensis, 2016)
The aim of this study was to assess how the steadily increasing concentration of a physiologically important element, magnesium, can affect the content of certain nutritional elements in the leaves of the hydroponic cultivated lettuce (Lactuca sativa convar. capitata L.). The nutrient elements nitrogen, magnesium and calcium were determined in the leaves of lettuce after supplementation with magnesium. Increasing magnesium concentration in the nutrient solution caused decrease of nitrogen content of dry matter in the leaves from 4.94 m/m% to 4.39 m/m%. The concentration of magnesium increased from 0.303 m/m% to 0.571 m/m%, and that of calcium decreased from 0.723 m/m% to 0.358 m/m%, in the average of 4 repetitions. Increasing concentration of magnesium can be the consequence of increased amounts of magnesium supplemented while decrease of nitrogen and calcium can be explained by the phenomenon of attenuation.